Effects of operational disruptions on corrosion of seabed chains and associated microbial community in offshore mooring systems - Sørensen, Ketil Bernt; Tiano, Laura; Molid, Solfrid; Gabrielsen, Øystein; Liengen, Turid (Frontiers in Microbiology, 2026)
IntroductionThe longevity and operational reliability of offshore mooring chains are critical for the safety of floating oil and gas installations. These chains are subjected to harsh marine environments and numerous stress factors, such as microbiologically influenced corrosion (MIC). This study focuses on MIC on seabed chains under different environments: embedded in sediment or lifted into the water column.MethodsMicrobial communities and corrosion rates on seabed chains were studied during periods of normal operation, with the chains placed with one end in the water column and the other end anchored inside the sediment, and resting periods where the entire seabed chain was on the seabed or buried within. Corrosion rates were measured, and deposits of corrosion products and scale on the seabed chains were studied by microbiological and chemical analysis.ResultsDuring the study period, microbial communities, including groups of potentially MIC-causing Bacteria and Archaea, were present in the scale material deposited on the surface of the seabed chains. Corrosion rates varied significantly both with time and along the length of the seabed chains, but although the corrosion was at least partly ascribed to MIC, there was no obvious correlation between corrosion rates and numbers of microorganisms present in the local deposits.DiscussionSeveral biological and chemical mechanisms are discussed in this paper. The data indicates that complex biogeochemical reactions were contributing to the observed corrosion, including several different biological pathways and types of S- and Fe-cycling, formation of protecting mineral layers and distribution of anodic and cathodic sections locally along the length of the seabed chains. Our findings emphasize the dynamic and unpredictable role of microbial communities, driving complex and spatially structured corrosion.